Consumer Acceptance on The Grilled Catfish (Pangasius hypophthalmus) in Different Smoking Materials and Methods - Raja Tayib; N Ira Sari; Tjipto Leksono (Universitas Djuanda, 2021)
This study aimed to observe the effect of different smoking materials and methods on the consumer acceptance on the grilled catfish. The grilling treatments were consisting of grilling the fish by using coconut shell (A1), grilling the fish by using coconut shell charcoal (A2) and roasting the smoke flavored fish by using an oven (A3). The parameters observed were sensory evaluation, total bacteria plate count, the value of water activity, the content of total phenol and total acid. The result showed that the grilling the catfish by using coconut shell was indicated the most preferred by consumers. The product was showing the highest quality, characterized by the intact and shiny appearance, distinctive aroma of roasted fish, strong grilled fish taste, compact and dry solid texture. The number of total bacteria was 1.4 x 104 CFU/g, the value of water activity was 0.84%, pH was 6.3, the content of total phenol was 32.67 ppm and the total acid was 1.75%.Keywords: catfish, coconut shell, grilling, liquid smoke